Involvement of Multiple Transporters-mediated Transports in Mizoribine and Methotrexate Pharmacokinetics - Teruo Murakami; Nobuhiro Mori (MDPI AG, 2012)
Mizoribine is administered orally and excreted into urine without being metabolized. Many research groups have reported a linear relationship between the dose and peak serum concentration, between the dose and AUC, and between AUC and cumulative urinary excretion of mizoribine. In contrast, a significant interindividual variability, with a small intraindividual variability, in oral bioavailability of mizoribine is also reported. The interindividual variability is mostly considered to be due to the polymophisms of transporter genes. Methotrexate (MTX) is administered orally and/or by parenteral routes, depending on the dose. Metabolic enzymes and multiple transporters are involved in the pharmacokinetics of MTX. The oral bioavailability of MTX exhibits a marked interindividual variability and saturation with increase in the dose of MTX, with a small intraindividual variability, where the contribution of gene polymophisms of transporters and enzymes is suggested. Therapeutic drug monitoring of both mizoribine and MTX is expected to improve their clinical efficacy in the treatment of rheumatoid arthritis.